2020
DOI: 10.1021/acs.oprd.0c00325
|View full text |Cite
|
Sign up to set email alerts
|

Renewable Solvents for Palladium-Catalyzed Carbonylation Reactions

Abstract: Solvents constitute the largest component for many chemical processes and substitution of nonrenewable solvents is a longstanding goal for green chemistry. Here, we show that Pd-catalyzed carbonylative couplings, such as carbonylative cross-couplings, aminocarbonylations, and alkoxycarbonylations, can be successfully realized using renewable solvents. The present research covers not only well-established renewable solvents, such as 2-methyltetrahydrofuran (2MeTHF), limonene, and dimethyl carbonate, but also re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 91 publications
0
22
0
1
Order By: Relevance
“…It was found that aminocarbonylation proceeded well in DMC while alkoxycarbonylation was successfully conducted in DMC and 2-MeTHF. 333 …”
Section: Common Reactions In Dipolar Aprotic or Ethereal Solvents Rep...mentioning
confidence: 99%
“…It was found that aminocarbonylation proceeded well in DMC while alkoxycarbonylation was successfully conducted in DMC and 2-MeTHF. 333 …”
Section: Common Reactions In Dipolar Aprotic or Ethereal Solvents Rep...mentioning
confidence: 99%
“…Numerous reports 23,33,46,47 outlining the aminocarbonylation of aryl (psuedo)halides typically describe the use of between 1 to 3 equivalents of CO surrogate. To determine if the transformation of 15 to carboxamide 16 could be achieved with less than 10 equivalents of CO, our attention turned to reducing the number of equivalents of our chosen CO surrogate (formic acid, mesyl chloride, and triethylamine) 33 with respect to aryl iodide 15 (Table 3), while keeping all other variables constant including the COware ® apparatus volume (20 mL).…”
Section: Paper Synthesismentioning
confidence: 99%
“…8). 2020 年, Bayer 等 [31] 报道了一种绿色、环保的合成 二芳基甲酮类化合物的方法. 他们以溴代芳烃和芳基硼 酸类化合物为原料, 乙酰丙酮钯为催化剂, 二(1-金刚烷 基)-正丁基膦氢碘化物(CataXCium AHI)为配体, 氢氧 化钠为碱, 9-甲基-9H-芴-9-羰基氯(COgen)为羰基源, 在 柠檬烯中反应 18 h 左右可制得二芳基甲酮类化合物, 收 率达 96%, 该反应底物适用性广泛, 同时适用于芳甲酰 胺、芳酸酯类化合物的合成.…”
Section: 他们对反应机理进行了推测(以 N-取代吡咯为例)unclassified